Financial Programming and Policy : The Case of Sri Lanka - Karlik, John (International Monetary Fund, 1996)
This book, by a staff team in the IMF Institute, contains a series of workshops that introduce the process of formulating a hypothetical macroeconomic and structural adjustment program, which is a central element in the financial programming courses offered by the IMF Institute. In addition to elaborating key concepts for the four major sectoral accounts, the workshops are designed to allow the development of a step by step reference scenario for Sri Lanka.